Intelligence Report - Clerical & Supervisory Workers in the Port of London, 6 May 1926 (United Kingdom)
1926-05-06 "Intelligence Report - Clerical & Supervisory Workers in the Port of London, 6 May 1926" [g0795001.jpg], 6 May 1926 Local Organisation